Implementing resilience-based interventions for healthcare employee well-being: evidence from the pandemic crisis - Kosycarz, Ewa Agnieszka; Juszczak, Dorota; Raulinajtys-Grzybek, Monika; Krejner-Nowecka, Anna (Frontiers in Public Health, 2025)
IntroductionOrganizational resilience is of paramount importance for coping with adversity, particularly in the healthcare sector during crises. The objective of the present study was to evaluate the impact of resilience-based interventions on the well-being of healthcare employees during the pandemic. In this study, resilience-based interventions are defined as organizational actions that strengthen a healthcare institution’s capacity to cope with crises—such as ensuring adequate personal protective equipment and staff testing, clear risk-communication, alternative care pathways (e.g., telemedicine) and psychosocial support—each mapping onto the recognized resilience capabilities of material resources, information management, collateral pathways and human-capital management The research question focused on two key aspects: first, whether Polish healthcare institutions effectively implemented these interventions, and second, how these interventions were perceived by their employees. The hypothesis tested was that resilience-based interventions positively influence employee well-being.MethodsThe study was conducted between August 21, 2020, and October 6, 2020, in Poland (across all regions). It utilized a cross-sectional, online survey-based approach, targeting healthcare professionals. A 39-item questionnaire was developed and distributed via Microsoft Forms, with participants recruited through websites and newsletters from doctors, nurses, and midwives’ associations. A variety of statistical methods were used to analyze the obtained data, i.e., logistic regression, proportional ordinal logistic regression, multiple marginal independence test, simultaneous pairwise marginal independence test, Cochran Q test, random forest-based imputation of missing data.ResultsThe study found that resilience-based interventions, such as access to personal protective equipment and virus-detection testing, significantly reduced anxiety among healthcare workers. The study indicated a deficiency in employer-provided psychological support. Furthermore, it demonstrated that an increase in workload does not necessarily lead to an increase in employee expectations of recognition and appreciation. Overall, this study underscores the importance of comprehensive managerial strategies in maintaining organizational resilience and improving employee well-being during crises.DiscussionThis study shows that resilience-based management—especially reliable PPE, testing, and clear internal communication—helps protect healthcare workers’ well-being during crises. Strengthening communication and psychological support before future emergencies remains essential. The findings echo existing research and lay groundwork for further work on healthcare resilience and staff well-being.